PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN PT. SAMPURNA KUNINGAN JUWANA, DI KABUPATEN PATI) - Ika Nur Cahyaningrum; Agung Budiatmo (Universitas Diponegoro, 2019)
Quality of human resources is one of the key factors for business success. Based on the data obtained, the performance of the employees at PT.Sampurna Kuningan Juwana tends to decline in 2017. Through preliminary study done it can be founded the decreasing of job satisfaction related with compensation and work environment. So that, the decreasing of job satisfaction ultimately can cause decreasing in employee’s performance. This type of research is explanatory research. Sampling used is a saturated sampling technique with 55 respondents who are employees of PT. Sampurna Kuningan Juwana. The technique of collecting data used questionnaires, interviews, and literature. This study used qualitative and quantitative analysis with validity, reliability, comparison coefficients, coefficient of determination, regression analysis, t test with the help of IBM SPSS version 21.0 program and sobel analysis to find the effect of intervention variable. Based on the analysis results, it is concluded that compensation and work environment could give significant affect to job satisfaction, job satisfaction could give significant affect to employee’s performance, job satisfaction can mediate compensation performance with employee’s performance as a full intervening variable and can mediate work environment with employee’s performance as a partial intervening variable. The suggestions that given in order to improve employee’s performance are also consider to the employee's assessment of the head expenditure policy not only depending on the working period but also on the work ability of the employee, as well as the determination of the amount of compensation for individual performance. To improve a good work environment by maintaining existing facilities, and need intensive training to improve employee competencies so that it will improve employee job satisfaction which ultimately improves employee performance.